The fault systems that control the occurrences of iron ore deposits in northeastern Aswan, Egypt - Mohamed Abd El-Wahed; Ibrahim A. Salem; Mohamed Attia; Dina Younis (Scientific Reports)
Abstract The present study combines remote sensing data (Landsat-8 and ASTER) with structural analysis to identify the fault systems affecting the distribution of the ironstone beds in northeastern Aswan, Egypt. Sedimentary rocks, such as the Abu Aggag, Timsah, and Umm Brammily formations, characterize northeastern Aswan. The Abu Aggag Formation consists of kaolinitic conglomerate, conglomeratic sandstone, and mudstone. The upper Timsah Formation consists of ferruginous sandstones, oolitic ironstone, and mudstone. Fluvial sandstone forms the Umm Brammily Formation. The oolitic sandy ironstone (2–2.5 m thick) is rich in dark red oolitic hematite and goethite. The ironstone deposit ranges in composition from oolitic sandy ironstone to oolitic ironstone. The distribution of iron minerals is extremely consistent with the iron concentration grade indicated by the Landsat-8 and ASTER Brand Ratios. Five main fault sets to control the extension of the ironstone beds: NNE-SSW left-lateral strike-slip faults (set 1); ENE-WSW normal faults (set 2); NNW-SSE normal faults (set 3); NW–SE normal faults (set 4); and NE-SW normal faults (set 5). The subsequent displacement of Set 3 faults increased the depth of the ironstone bed, which raised the sedimentary overburden load and increased the cost of ironstone exploitation, as well as the absence of iron ore exploitation zones bordering the Nile River.